[tex]1.a=\frac{1}{\sqrt{(5-3\sqrt3)^2}}-\frac{2}{\sqrt{(2\sqrt3-4)^2}}\\
a=\frac{1}{|5-3\sqrt3|}-\frac{2}{|2\sqrt3-4|}\\
a=\frac{1}{3\sqrt3-5}-\frac{2}{4-2\sqrt3}\\
a=\frac{3\sqrt3+5}{2}-\frac{2(4+2\sqrt3)}{4}\\
a=\frac{3\sqrt3+5}{2}-\frac{4+2\sqrt3}{2}\\
a=\frac{3\sqrt3+5-4-2\sqrt3}{2}\\
a=\frac{\sqrt3+1}{2}\\
(a)^{-1}=\frac{2}{\sqrt3+1}\\
\frac{1}{a}=\frac{2(\sqrt3-1)}{2}\\
\frac{1}{a}=\sqrt3-1[/tex]
[tex]2.l=\frac{5}{12}*L\\
l=\frac{5}{12}*60\sqrt3\\
l=25\sqrt3\\
A=l*L\\
A=25\sqrt3*60\sqrt3\\
A=4500cm^2[/tex]